2022
DOI: 10.3390/diagnostics12061406
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Based Prediction of Oroantral Communication after Tooth Extraction Utilizing Preoperative Panoramic Radiography

Abstract: Oroantral communication (OAC) is a common complication after tooth extraction of upper molars. Profound preoperative panoramic radiography analysis might potentially help predict OAC following tooth extraction. In this exploratory study, we evaluated n = 300 consecutive cases (100 OAC and 200 controls) and trained five machine learning algorithms (VGG16, InceptionV3, MobileNetV2, EfficientNet, and ResNet50) to predict OAC versus non-OAC (binary classification task) from the input images. Further, four oral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Tobel et al also demonstrated that practitioners with 5 to years of experience were capable of achieving results similar to the AI algorithms [28]. Our previous study on the prediction of OAC in OPGs was able to confirm this observation [16]. Kim et al developed similar protocols to predict the existence of inflamed maxillary sinuses.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Tobel et al also demonstrated that practitioners with 5 to years of experience were capable of achieving results similar to the AI algorithms [28]. Our previous study on the prediction of OAC in OPGs was able to confirm this observation [16]. Kim et al developed similar protocols to predict the existence of inflamed maxillary sinuses.…”
Section: Discussionmentioning
confidence: 60%
“…In addition to buccal advancement flap, rotation flaps with buccal cheek fat, local flap plastics with gingival tissue or substitute materials, and various different local rotation flaps, new techniques such as plated rich fibrin, which induces increased wound healing, are increasingly being discussed in the literature [9,25,26]. As we have found in a prior study, we were unable to obtain satisfactory results when using panoramic radiographs to predict OAC [16]. The object of this study was to identify classification systems that were significantly associated with an increased probability of occurrence of OAC.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations